Paul meets Muhammad a Christian-Muslim debate on the resurrection - Licona, Michael R., 1961- (Grand Rapids, MI Baker, 2006)
Includes bibliographical references.
Keywords: Muhammad, Prophet -- d. 632; Jesus Christ -- resurrection; Paul, the apostle, Saint; Christianity and other religions -- Islam; Islam -- relations -- Christianity